Assessing the effectiveness of the Public Procurement Act 2003 (ACT 663) of Ghana on the management of procurement operations of University of Education, Winneba - Okyere, Stephen (2014)
A thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirement for the award of Master of Business Administration (Logistics & Supply Chain Management),